PERENCANAAN DESAIN DERMAGA TUKS PLTU (4X7) MW LOKASI SORONG KABUPATEN SORONG, PROVINSI PAPUA BARAT - Effendi, Totok Firman; Marsudi, Suwanto (Jurnal Mahasiswa Jurusan Teknik Pengairan, 2019)
ABSTRAK:Indonesia merupakan salah satu negara maritim terbesar dengan luas laut 63 % dari luas total keseluruhan negara Indonesia.  Sehingga pelabuhan cukup berperan penting dalam upaya pembangunan nasional.  Seiring majunya pembangunan nasional di daerah Papua, permintaan akan kebutuhan energi terutama energi listrik terus meningkat.  Untuk mengatasi hal ini, diperlukan pembangunan pembangkit listrik guna memenuhi kebutuhan yang ada.  Oleh sebab itu, didaerah Sorong direncanakan akan dibangun PLTU (4x7) MW dengan batu bara sebagai bahan bakar.  Batu bara tersebut akan di distribusikan mengunakan kapal tongkang 10.000 DWT.  Sehingga diperlukan sebuah dermaga khusus (TUKS) untuk kapal tersebut.  Untuk perencanaan dermaga menggunakan data angin selama 10 tahun (2006-2015), data pasang surut (15 hari), dan data tanah (hasil uji SPT).  Perencanaan dermaga dimulai dengan pembangkitan gelombang oleh angin menggunakan metode JONSWAP.  Analisis gelombang rencana menggunakan distribusi Fisher-Tippet I dan didapatkan tinggi gelombang rencana maksimum kala ulang 50 tahun sebesar 1,270 m arah utara.  Muka air rencana +4,136 m dengan tinggi gelombang pecah maksimum 1,350 m arah utara dengan kala ulang 50 tahun.  Struktur dermaga  direncanakan memiliki dengan panjang 170 m, lebar 20 m, dan kedalaman 14 m.  Hasil uji SPT didapatkan jenis tanah pada lokasi dermaga yaitu lempung berpasir dengan kedalaman tanah keras pada kedalaman lebih dari 12 m.  Dimensi balok melintang tebal 0,75 m x 0,5 m dengan panjang 20 m dan berjumlah 36 buah.  Dimensi balok memanjang 0,5 m x 0,3 m dengan panjang 170 m dan berjumlah 9 buah.  Tebal plat 0,4 m dan tebal aspal 0,05 m.  Untuk tiang pancang menggunakan tiang pancang spun pile berdiameter 0,8 m dan panjang 27 m berjumlah 180 buah.  Untuk menahan gaya lateral dermaga, diperlukan tiang pancang miring.  Dalam perencanaan dermaga ini, tiang pancang miring diletakkan pada bagian belakang dermaga dengan kemiringan tiang 300.ABSTRACT: Indonesia in one of the most largest maritime countries wint an seas area 63 % of total indonesia area.  The port plays on important role in national developed efforts.  As national developed advance in the Papua region, demand of energy continues increase, especially electricity energy.  To overcome this, the construction of a power plan is needed for supply the energy.  Therefore in Sorong area will built an power plan (4x7) MW with coal as fuel.  The coal will be distributed using 10.000 DWT ship barge.  That will needed special port for self-interest for this ship can dock.  For pier planning using 10 years of wind date (2006-2015), tidal date (15 days), and soil date (SPT test result).  Pier planning begins with wave generated by using JONSWAP method.  The wave planned analysis uses the fisher-tipped I distribution and the height wave palnned of 50 years return period is 1,270 m northward.  The design water lever is +4,136 m with maximum breaking wave 1,350 m height northward with 50 years return period.  The pier structure planned has lenght 170 m, wide 20 m, and depth 14 m.  The result of SPT test found that soil in location is sandy clay with hard soil depth at depth more than 12 m.  The dimension of transverse beam are 0,75 m x 0,5 m thick with a lenght 20 m and total beam 36 pieces.  The dimension of extends beam are 0,5 m x 0,3 m thick with lenght 170 m and total beam 9 pieces.  Plate thickness is 0,4 m and asphalt thickness is 0,05 m.  For pile is using spun pile with diameter of 0,8 m and lenght 27 m totaling 180 pieces.  To hold the lateral force of the pier, raking  pile is needed.  In planing this pier, the raking pile are placed in the back of pier with slope 300.ABSTRACT: Indonesia in one of the most largest maritime countries wint an seas area 63 % of total indonesia area. The port plays on important role in national developed efforts. As national developed advance in the Papua region, demand of energy continues increase, especially electricity energy. To overcome this, the construction of a power plan is needed for supply the energy. Therefore in Sorong area will built an power plan (4x7) MW with coal as fuel. The coal will be distributed using 10.000 DWT ship barge. That will needed special port for self-interest for this ship can dock. For pier planning using 10 years of wind date (2006-2015), tidal date (15 days), and soil date (SPT test result). Pier planning begins with wave generated by using JONSWAP method. The wave planned analysis uses the fisher-tipped I distribution and the height wave palnned of 50 years return period is 1,270 m northward. The design water lever is +4,136 m with maximum breaking wave 1,350 m height northward with 50 years return period. The pier structure planned has lenght 170 m, wide 20 m, and depth 14 m. The result of SPT test found that soil in location is sandy clay with hard soil depth at depth more than 12 m. The dimension of transverse beam are 0,75 m x 0,5 m thick with a lenght 20 m and total beam 36 pieces. The dimension of extends beam are 0,5 m x 0,3 m thick with lenght 170 m and total beam 9 pieces. Plate thickness is 0,4 m and asphalt thickness is 0,05 m. For pile is using spun pile with diameter of 0,8 m and lenght 27 m totaling 180 pieces. To hold the lateral force of the pier, raking pile is needed. In planing this pier, the raking pile are placed in the back of pier with slope 300.